A Rare Complication of Sequential Bilateral Posterior Knee Dislocation Following Bilateral Robotic Assisted Primary Knee Replacement: Case Report - Deepak D Chitragar; Sathish Devadoss; Annamalai Devadoss (Journal of Orthopaedic Case Reports)
Introduction: To date, there have been no documented cases of sequential bilateral posterior knee dislocation following robotic-assisted bilateral total knee arthroplasty (TKA) in the literature. Robotic-assisted TKA is gaining traction due to its potential advantages in precision and patient outcomes. Sequential bilateral TKA offers several benefits, Nevertheless, complications can still arise, some of which are rare and difficult to manage. One such complication is posterior tibiofemoral dislocation after primary TKA, can lead to severe consequences and is influenced by various patient-related and surgeon-related risk factors, we present case of rarest of rare sequential knee dislocation and challenges in managing such a case, bring awareness about the risk factor to surgeons. Case Report: A 65-year-old woman presented with an atraumatic posterior knee dislocation 3 months after undergoing robotic-assisted total knee replacement (TKR) 8 months earlier. The right knee was managed with extensive hamstring release and the debridement, antibiotics, and implant retention technique with change of poly insert, while the left knee was treated with knee arthrodesis. The underlying cause of these complications was identified as patient-related neuropsychiatric illness accompanied by hypertonia. Conclusion: Posterior knee dislocation is a rare complication that can occur even after robotic-assisted TKR. The occurrence of sequential bilateral dislocation is exceptionally uncommon and presents significant management challenges. It is crucial to consider patient-related factors, such as neuropsychiatric disorders, when planning robotic TKR. A thorough neuropsychiatric evaluation is essential for selecting candidates for bilateral procedures to ensure optimal outcomes and patient satisfaction following robotic TKR.